Organização e funcionamento do programa sala de leitura nas escolas da diretoria de ensino de Presidente Prudente - Batista, Josany Leme da Silva [UNESP] (2015)
This paper is entailed to the research line Childhood and Education of the Pot-Graduation Program in Education of FCT/UNESP, Presidente Prudente, and for this reason it aims to understand as the Sala de Leitura (reading room) program, implemented in São Paulo State since 2009, works in public schools from the Regional Board of Education of Presidente Prudente - SP. For this purpose it is pivotal understanding which factors are necessary for this space to consolidate in its activities, once they were the justifying of its creation. In the schools, there is an area reserved to the organization of a school library based on legal principles, for this reason it must meet the assignments for what it was created, in other words, being a place which provides access to books and other materials for information and enjoyment. There is little literature that approaches this issue, even though the program exists in São Paulo State since 2009, no relevant studies sought to map the schools from the Regional Board of Education of Presidente Prudente, analyze the reading actions that happen in there and trace the profile of the professional who works in this environment. In order to implement this study, it was first developed a bibliographical research, which consisted of moment to reflect about the legislation which rules the Sala de Leitura program and the selection and performance criteria of the professional who works in this space...